2013
DOI: 10.1080/19443994.2013.773861
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence vs. classical approaches: a new look at the prediction of flux decline in wastewater treatment

Abstract: A B S T R A C TThis study compares the performance of three different approaches to modeling namely the classical pore-blocking models, artificial neural networks (ANN) and the novel genetic programming (GP) approach. Among the available models proposed by Hermia, standard poreblocking and cake filtration models were opted because of their better fitness with experimental measurements. A feedforward backpropagation network using Bayesian Regulation as well as Levenberg-Marquardt training methods was developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 33 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Additionally, conventional models typically require knowledge of a priori information about the system, such as the nature of the foulants or the fouling mechanism, which may not always be available [ 41 ]. Therefore, AI-based models have been increasingly used to predict membrane fouling because they can learn from data, find complex patterns, and make accurate predictions [ 42 , 43 ]. They can be trained on historical data of membrane filtration processes, including operating conditions, membrane properties, and feed characteristics, to predict the fouling rate [ 17 ].…”
Section: Membrane Fouling Prediction Modelsmentioning
confidence: 99%
“…Additionally, conventional models typically require knowledge of a priori information about the system, such as the nature of the foulants or the fouling mechanism, which may not always be available [ 41 ]. Therefore, AI-based models have been increasingly used to predict membrane fouling because they can learn from data, find complex patterns, and make accurate predictions [ 42 , 43 ]. They can be trained on historical data of membrane filtration processes, including operating conditions, membrane properties, and feed characteristics, to predict the fouling rate [ 17 ].…”
Section: Membrane Fouling Prediction Modelsmentioning
confidence: 99%
“…The challenges to describe mechanistically such a combination of the many synergistic physico-chemical phenomena occurring during fouling have steered the research community to explore purely data-driven approaches (e.g., artificial intelligence/machine learning, AI/ML) 5,17,21,22 . Niu et al 5 recently reviewed the state-of-the-art AI/ML applied to predict water flux and other performance parameters in membrane processes during fouling.…”
Section: Introductionmentioning
confidence: 99%
“…Several algorithms have been explored, with artificial neural networks being the most employed 5 . Focusing on ultrafiltration, different researchers previously concluded that AI-based modeling approaches provide better predictive accuracy compared to mechanistic models, such as poreblocking 21,22 and Hermia's models 23,24 .…”
Section: Introductionmentioning
confidence: 99%